The Barriers in Implementing Electronic Prescribing in The Health Care: a Systematic Review - Leawaty, Leawaty; Wibowo, Adik (UHAMKA Press, 2018)
Medication error remain extremely common, and the health care system can do much more to prevent it. Electronic prescribing is increasingly being viewed by health care stakeholders as an important step toward improved medication safety, better management of medication costs, increased practice efficiency, and improved health care quality. However, the adoption of e-prescribing has been difficult to attain owing to numerous barriers throughout the industry. Even with all the benefits of e-prescribing, many providers and pharmacists remained hesitant about completely adopting an e-prescribing system. The main purpose of this study was to explore and to assess the barriers of electronic prescribing implementation. The methodology for this study followed the basic principles of a systematic review with PRISMA methode retrieved from online database PubMed using a keyword “barriers” OR “obstacles” AND “electronic prescribing” OR “electronic prescription” AND “implementation”. Finally 6 documents were selected by full text inclucion and assessed for eligibility. The result of the study are  inefficiency, the low uptake of the physicians, the cost of implementing the electronic prescription, system errors and the privacy and legacy. The conclusion from the studies should that electronic prescribing implementation barriers those we divided into 2 groups : the user factors and the system factors of the electronic prescription. Vendors or the consultants to facilitate more adequately the adoption of e-prescribing by giving the physicians the free trial and provide evaluation and improvement according to the physicians' needs for the features in the e-prescription.